Solutions Of The Rational Difference Equations X(n+1)=x(n-3)/(1+x(n)x(n-1)x(n-2)) - D. Şimşek; M. Eröz (MANAS: Journal of Engineering)
In this paper a solution of the following of difference equations is examined, X(n 1)=x(n-3)/(1 x(n)x(n-1)x(n-2)) (1)where the initial conditions are positive real numbers.